Bibliometric Analysis of Religious Communication in the Digital Age: Mapping the Scholarly Landscape from Mosque to Metaverse (2015-2024) - Firmasari, Desi; Mukhlizar; Fitriani, Riri; Samudra, Imam; Pakpahan , Fransiskus Novrianto (Business and Investment Review, 2024)
The 21st century's digital transformation is profoundly reshaping religious communication, migrating practices from physical spaces like mosques to digital and immersive environments. This study conducts a comprehensive bibliometric analysis to map the scholarly evolution of religious communication, specifically focusing on the transition from traditional settings to virtual reality (VR) and the Metaverse between 2015 and 2024. Using data from 565 Scopus-indexed publications, this research employs co-citation and bibliographic coupling analyses in VOSviewer to identify the field's intellectual structure and emerging research fronts. The findings reveal a diverse knowledge base, anchored in foundational theories like Bourdieu's social concepts and key technological frameworks from Augmented Reality (AR) to real-time spatial computing. Contemporary research clusters are converging around AI-driven intelligent systems and digital frameworks for heritage preservation. Despite this growth, the field is limited by a reliance on English-language, Open Access literature. The study concludes by proposing a multi-faceted future research agenda, urging exploration into the ethical integration of AI and IoT in religious practice, the development of faith-specific AR/VR frameworks, the establishment of religious UX principles, and the empirical measurement of "digital religious capital" within new algorithmic authority structures.